Constant installation of present orientation and safety (CIPOS) - subjective and physiological effects of an ultrashort-term intervention combining both stabilizing and confrontational elements - Stingl, Markus; Sammer, Gebhard; Hanewald, Bernd; Zinsser, Franziska; Tucha, Oliver; Pape, Valeska Reichel (Frontiers in Psychology, 2022)
Objectives Constant Installation of Present Orientation and Safety (CIPOS) is a Eye Movements Desensitization and Reprocessing (EMDR)-derived technique, which is often used to prepare for the treatment of post-traumatic stress disorder (PTSD). It differs from the latter by involving cyclically recurring exercises in reorientation to the present, interspersed between brief periods of exposure to the traumatic material. While EMDR is well established as a therapeutic method, the efficacy and mechanisms of action of CIPOS have not been investigated so far. In this pilot study, an experimental setting was used to record the subjective and physiological effects of the CIPOS intervention compared to a control condition with pure mental exposition. Methods The study was performed on 30 healthy volunteers aged from 20 to 30 years. Distress was induced using audio files of subjectively stressful situations. Subjective distress was measured via the Subjective Units of Distress Scale (SUD), while physiological indicators (noise-induced startle reflex, skin conductance level) were used as measures for objective stress. For each condition, pre- and post-intervention comparisons were calculated. Results In both groups, startle reflex potentiation and mean skin conductance level significantly decreased. In the group with CIPOS intervention, but not in the control group, a significant decrease in the SUD value was found. Conclusion and significance The results show that the CIPOS technique is as effective as pure mental exposition in reducing physiological stress. In addition, a superiority in reducing subjective distress (indicating a simplified reassessment of the stressful material) was found compared to pure mental exposition. Possible explanations of these effects are discussed.